Ordenamentos jurídicos educacionais no período de pandemia e pós-pandemia no Brasil, no estado do Tocantins em específico na cidade de Palmas - Ramos, Wanessa Ribeiro (Universidade Federal do Tocantins, 2023)
The present work seeks to bring the Educational Legal Orders created in the Pandemic and Post-Pandemic period to serve basic education students in the state of Tocantins, specifically in the city of Palmas. The research consists of reflecting on the actions and programs elaborated through legislation, ordinances and decrees, the measures that were created to guarantee access to education for children in basic education. The general objective of the research is to investigate the educational Legal Orders created during the Pandemic and Post-pandemic period, to present each one of them and to analyze the actions carried out by the education secretariats of the state of Tocantins and in the city of Palmas. The methodology used was a qualitative bibliographic and documentary research, investigations were carried out on the subject, through official websites that make the legislation available, such as the Planalto website and the Ministry of Education website, as well as several articles and books by authors such as: Dias and Matos (2012); Bucci (2001); Bucci (2006); Souza, Gonçalves and Jorge (2021); Carmo e Rocha (2014) and Tenório, Ferreira e Souza (2021). Through several investigations collected, a compilation of information was carried out about Educational Policies during the Pandemic and Post-pandemic linked to the legislation carried out in their respective periods and at the end I carry out a reflection on the confrontation and the impacts caused in the area of education in the State of Tocantins in the city of Palmas.